Rancang Bangun Sistem Penyiraman Tanaman Otomatis Dan Pendeteksi Kondisi Tanah Menggunakan Soil Moisture Berbasis Arduino - Syarif, Irwan; Tahir, Tamus Bin; L, Nurlia; Yunendar, Wakhid (Patria Artha Technological Journal, 2021)
Design Automatic Watering System and Soil Condition Detection Using Arduino Based Soil Moisture. Watering plants is closely related to the needs of water with different levels. This will of course affect the frequency and quantity of its watering. If planted in pots, the same plants (their type and age) will require a more frequent frequency of watering than plants that grow directly from the soil. This research aims to design and implement automatic watering system and soil condition detection using Arduino-based soil moisture.  The type of research that is implemented when testing on this system is done by means of direct testing or simulation of tools that work automatically in accordance with the working principles of each tool